The Role of Interactive Technologies in Open Distance Learning - Pandansari, Purwosiwi; Lek, Siri; Krit, Pong (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The expansion of Open Distance Learning (ODL) in recent years has highlighted the need for interactive technologies that support student engagement, knowledge retention, and personalized learning. As ODL environments often lack face-to-face interaction, interactive technologies like virtual classrooms, discussion forums, and gamified learning tools play a critical role in creating immersive learning experiences. This research aims to explore the impact of interactive technologies on student outcomes in ODL, focusing on engagement, satisfaction, and academic performance. A mixed-methods approach was used, combining quantitative surveys with qualitative interviews to capture students’ experiences with interactive tools in ODL. Data was collected from a diverse sample of students enrolled in online programs, and statistical analysis was applied to measure correlations between interactive technology usage and learning outcomes. The qualitative data provided insights into student perspectives on the benefits and challenges of using interactive tools. Findings indicate that students who actively engage with interactive technologies report higher levels of motivation and satisfaction compared to those who rely solely on traditional online resources. Interactive tools also appear to facilitate better knowledge retention and a sense of community among distance learners. However, challenges such as accessibility and technological support remain barriers to effective usage. The study concludes that interactive technologies enhance the ODL experience by promoting active learning and improving overall educational outcomes. Further research is recommended to explore scalable solutions for integrating these tools, particularly in under-resourced settings, to ensure equitable access for all students.